A Meta-Analysis of the Effect of Sodium Glucose Cotransporter-2 Inhibitors on Metabolic Parameters in Patients With Polycystic Ovary Syndrome - Sinha, Binayak; Ghosal, Samit (Frontiers in Endocrinology, 2022)
Objective: Polycystic ovary syndrome (PCOS) is the most common endocrinopathy among women of childbearing age and is associated with multiple morbidities. However, treatment for this condition is mainly applied for symptomatic relief and does not address the complex pathophysiology of this condition. This meta-analysis was conducted on the usage of sodium-glucose cotransporter 2 inhibitors (SGLT-2is) in PCOS because this group of drugs presents an attractive strategy to address the metabolic and hormonal defects by managing the pathophysiological defects observed in this syndrome. Methods: We included prospective trials that enrolled patients with established PCOS and compared an SGLT-2i group versus a control group with at least 2 weeks of follow-up. The standardized mean difference (SMD) was used for effect size estimation from individual studies and was pooled using the fixed effect model. Results: We included four trials with a pooled population of 158 patients with documented PCOS who received either an SGLT-2i or standard management. From a metabolic perspective, significant improvements were observed in the reduction in body weight (SMD: -0.68, 95% CI -1.16 to -0.19, <0.01), fasting plasma glucose (FPG) (SMD: -0.59, 95% CI -0.99 to -0.19, P<0.01), and insulin resistance as assessed with the HOMA-IR (SMD: -0.39, 95% CI -0.76 to -0.03, P=0.03). In addition, a significant improvement was noted in dehydroepiandrosterone sulphate (DHEAS) levels (SMD: -0.55, 95% CI -0.94 to -0.16, P<0.01). Conclusion: SGLT-2i use is associated with salutary outcomes of metabolic and anthropometric markers of PCOS and likely favourable hormonal effects.